Abnormally increased low-density granulocytes in peripheral blood mononuclear cells are associated with interstitial lung disease in dermatomyositis. Issue 1 (2nd January 2017) - Zhang, Sigong; Shen, Haili; Shu, Xiaoming; Peng, Qinglin; Wang, Guochun
Abstract: Objective : We previously found that neutrophil extracellular traps (NETs) were associated with interstitial lung disease (ILD) in dermatomyositis (DM) patients. However, it is unclear whether low-density granulocytes (LDGs), endowed with enhanced NET formation capabilities, contribute to the pathogenesis of ILD. This study aims to elucidate the relationship between LDGs and DM-associated ILD. Methods : We recruited 48 DM patients (28 with ILD) as well as 19 healthy volunteers for this study. The percentage of LDGs in peripheral blood mononuclear cells (PBMCs) was ascertained by flow cytometry. Plasma cfDNA was measured by using the Quant-iT PicoGreen dsDNA Kit and plasma LL-37 was tested by using the LL-37 ELISA kit. Results: The percentage of LDGs was 7.1 times higher in DM patients than in healthy controls. LDG percentage was 2.7 times higher in DM patients with ILD than in DM patients without ILD. Additionally, LDG percentage positively correlated with MYOACT lung disease activity scores, and NET/neutrophil-related marker levels (LL-37, cfDNA, MPO, and MMP-8) in the DM group were significantly higher than those in the control group. Conclusion : The abnormal increase of LDGs may exacerbate abnormal NET regulation and further contribute to the pathogenesis of ILD in DM patients by abnormally forming NETs.